Saving the great barrier reef - Healy, Justin (Issues in society, 2018)
As the largest coral reef system on the globe and home to 1,500 species of fish and other diverse marine life, Australia's Great Barrier Reef is unquestionably one of the great wonders of the natural world. Unfortunately, it is also in grave danger of dying. Recent annual back-to-back coral bleaching events have drastically accelerated the existing damage to the Great Barrier Reef and its rich biodiversity. The reef is under threat from numerous pressures, both natural and man-made. These threats include over-fishing, coastal development, agriculture, mining, tourism and the ravaging ecological impacts of climate change. How is Australia sustainably managing the reef and the land-based and sea life it supports? What conservation threats are being effectively addressed - is it too late to save the Great Barrier Reef? Also includes: worksheets and activities, fast facts, glossary, web links, index. Titles in the Issues in Society series are individual resource books which provide an overview on a specific subject comprised of facts and opinions. The information in this resource book is not from any single author, publication or organisation. The unique value of the Issues in Society series lies in its diversity of content and perspectives. The content comes from a wide variety of sources and includes: newspaper reports and opinion pieces, website fact sheets, magazine and journal articles, statistics and surveys, government reports, and literature from special interest groups.